Effects of Dietary Supplementation of Humic Acid Sodium and Zinc Oxide on Growth Performance, Immune Status and Antioxidant Capacity of Weaned Piglets - Wang, Qi (Animals (Basel), 2020)
SIMPLE SUMMARY: Weaning of piglets can destroy the piglet’s intestinal health and immune function, leading to diarrhea and a reduction in growth rate eventually. Considering drug resistance and residues, new alternatives, such as sodium humate (HNa), have attracted considerable research interest over recent decades. Our study was designed to explore the effect of HNa on the growth performance, diarrhea rate, antioxidative, inflammation, and immunity of weaned piglets and the possibility of HNa replacing antibiotics and zinc oxide. The obtained results indicate that HNa reduces stress, protects the intestinal barrier, and improves the performance of weaned piglets. ABSTRACT: At present, the widespread use of high-dose zinc oxide and antibiotics to prevent post-weaning diarrhea (PWD) in piglets has caused serious environmental problems. To solve this problem, we studied the effect of HNa as a substitute for zinc oxide (ZnO) and antibiotics on the growth performance, immune status, and antioxidant capacity of piglets. Seventy-two weaned piglets (body weight = 7.42 ± 0.85 kg, 26-d-old) were distributed in a randomized 2 × 3 factorial design (two sexes and three treatments) with six replicates of four piglets each. The three treatments were the control diet (basic diet), HNa diet (basic diet + 2000 mg/kg sodium humate), and ZoA group (basic diet + 1600 mg/kg zinc oxide + 1000 mg/kg oxytetracycline calcium). ANOVA and Chi-square tests were applied to compare the means (p < 0.05) between treatments. The results showed that body weight at 16 and 30 d and the average daily gain of piglets fed with HNa or ZoA were significantly higher (p < 0.05) than the control group. Supplementing HNa or ZoA significantly increased (p < 0.05) the level of immunoglobulin M and G, and reduced (p < 0.05) the concentration of inflammatory factors such as tumor necrosis factor-alpha (TNF-α), interleukins IL-6 and IL-1β, myeloperoxidase (MPO), and diamine oxidase (DAO). Furthermore, dietary HNa or ZnO significantly reduced (p < 0.05) the level of total antioxidant capacity (T-AOC) and malondialdehyde (MDA) compared with the control group. ZoA treatment showed an upward trend of IgA level and a downward trend of the concentration of lipopolysaccharide (LPS) and catalase (CAT). Overall, the study demonstrated that the addition of HNa in the diet partially replaced antibiotics and ZnO to improve the growth performance, immune function, and antioxidant capacity of weaned piglets, and maintained a good preventive effect on piglet diarrhea.